A School-Based Measure of Culturally Responsive Practices - Asil, Mustafa (Frontiers in Education, 2017)
This study aimed to address a gap in current research on cultural responsiveness by introducing the Culturally Responsive Practices for Māori Scale (CRPMS), a self-report instrument designed to measure schools’ culturally responsive practices in relation to Māori students. Within this paper, the development and analysis of the factorial structure and psychometric properties of CRPMS are presented. The validity evidence findings from this study supported the utility of CRPMS as a measure of cultural responsiveness for mainstream English-speaking New Zealand schools. Potential uses and applications of the CRPMS by researchers and educational stakeholders are discussed.